Assessing the multidimensional impact of community-based cattle feedlot programs in the Eastern Cape, South Africa - Slayi, Mhlangabezi; Zhou, Leocadia; Jaja, Ishmael Festus (Frontiers in Sustainable Food Systems, 2024)
Traditional cattle farming in the region faces numerous challenges, including limited market access, inadequate nutrition, and poor herd management, which hinder productivity and the livelihoods of farmers. This research explores whether structured feedlot programs can address these issues by enhancing agricultural productivity and improving farmer livelihoods. The study utilized quantitative data from 250 respondents and regression models to compare changes before and after participation in the feedlot programs. The findings reveal significant improvements in herd dynamics, with average herd size increasing by 40% and calving rates rising from 60% to 80%. Mortality and morbidity rates decreased by 50% and 47%, respectively. Regression analysis showed a positive impact on herd size (β = 20.00, p < 0.001) and a notable reduction in mortality (β = -0.30, p = 0.050). Animal performance also improved, with average daily gain (ADG) increasing by 60% and feed conversion ratio (FCR) improving by 25%. Health status was enhanced, indicated by a 50% reduction in disease incidence and an 80% increase in vaccination coverage. Regression results supported these improvements, showing significant positive effects of feedlot participation on ADG (β = 0.50, p < 0.001) and health status (β = -0.10, p < 0.005). Socio-economic benefits were also substantial, with household income increasing by 67% and new employment opportunities emerging. Food security improved significantly, with 85% of households reporting better access to food, and the average sales price per cattle increased by 50%. Regression analysis indicated strong positive impacts on household income (β = 1500, p < 0.001) and food security (β = 300, p = 0.010). Factors influencing farmer participation in the feedlot programs included perceived benefits (β = 0.80, p < 0.001), access to training (β = 0.50, p < 0.005), and market access (β = 0.70, p < 0.001), while the cost of participation negatively affected involvement (β = -0.002, p = 0.050). Overall, the study demonstrates that community-based cattle feedlot programs significantly enhance herd dynamics, animal performance, and socio-economic conditions for farmers in the Eastern Cape Province, offering a viable strategy for improving rural livelihoods and agricultural productivity.